Comprehension skills and reading tasks - Baldo, Alessandra (Revista Leitura, 2019)
This article reports data from a study into the separability of reading skills. Based on a study conducted by Alderson (1990), teachers of English as a foreign language were presented a list of reading skills and were asked to identify what three reading tasks were measuring in terms of the list. A comparison between the teachers’ responses and the objectives established by the author of the tasks has been interpreted as evidence of the unitary view of reading, as opposed to the multidivisible view of the process. DOI: 10.28998/0103-6858.2001n28-29p15-28